2020
DOI: 10.1186/s12941-020-00351-5
|View full text |Cite
|
Sign up to set email alerts
|

Ceftobiprole: a potential empirical post-operative monotherapy in prosthetic joint infections

Abstract: Background: This study aimed to evaluate in vitro susceptibility to ceftobiprole of clinical strains identified from prosthetic joint infections (PJIs) compared to that of the associations currently recommended for post-operative empirical antibiotic therapy (PEAT) (vancomycin with either cefepime, third-generation cephalosporin or piperacillin-tazobactam). Methods: We performed a 1-year retrospective study on all the surgical procedures performed in our hospital for PJI. Susceptibility profiles of all the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Other CRIOACs used alternative combinations (ceftriaxone/cefepime–vancomycin/daptomycin) for the postoperative probabilistic treatment of device infection. Ceftobiprole was chosen in this indication, with no resistance identified so far in any of the Staphylococcus species strains tested ( 29 ). However, our study showed an elevation of ceftobiprole MICs toward resistance in these LR-MDRSE strains.…”
Section: Discussionmentioning
confidence: 99%
“…Other CRIOACs used alternative combinations (ceftriaxone/cefepime–vancomycin/daptomycin) for the postoperative probabilistic treatment of device infection. Ceftobiprole was chosen in this indication, with no resistance identified so far in any of the Staphylococcus species strains tested ( 29 ). However, our study showed an elevation of ceftobiprole MICs toward resistance in these LR-MDRSE strains.…”
Section: Discussionmentioning
confidence: 99%